Bulk Magnetic Properties Arise from Micron‐Sized Supraparticle Interactions and Can be Modified on the Nanoscale - Wolf, Andreas; Heinlein, Markus; Kent, Noah; Müssig, Stephan; Mandel, Karl (Small, 2025)
Magnetic supraparticles (SPs) can be employed as micron-sized particulate additives in arbitrary objects to serve as ID-tag or recorder of environmental triggers. Combined with magnetic particle spectroscopy (MPS), which enables read-out of the magnetic information in ambient conditions within seconds, magnetic SPs represent a powerful approach to equip materials with information. The encoded information relies on magnetic interactions within the SPs (intra-SP interactions) of chosen nanoparticles (NPs). However, possible magnetic interactions between SPs (inter-SP interactions), that might alter the MPS signal as well, have been neglected so far. Herein, it is elucidated that significant inter-SP interactions exist and that they can be tailored via adjustments in the SP structure, i.e., by defined adjustments of their intra-interaction as revealed by 3D-MuMax simulations and experiments in viscous fluids. Superparamagnetic iron oxide nanoparticle-based SP powders with strong inter-SP interactions exhibit significantly different MPS signals compared to their state after being incorporated into a matrix. Powders with weak inter-SP interactions (achieved by integration of non-magnetic SiO2 nanoparticles) show almost no signal change before and after incorporation. Both extremes of inter-SP interactions can be beneficial for various application scenarios and can be tailored on the nano-scale due to the interdependency of intra- and inter-SP interaction
CRIS-Team Scopus Importer:2025-03-07
Keywords: magnetic interactions; magnetic particle spectroscopy; matrix interactions; supraparticles